(U. M)-derivations in completely semiprime ?-rings - Rahman, MM; Paul, AC (Bangladesh Journal of Scientific and Industrial Research, 2016)
The objective of this paper is to extend and generalize some results of (Rahman and Paul, 2014) in completely semiprime ?- rings. We prove that, if is an admissible Lie ideal of a completely semiprime ?-ring and d is a (U, M) -derivation of then d(u?v)=d(u)?v+u?d(v) for all u, v ? U and ? ? ? Mathematics Subject Classification: 13N15, 16W10, 17C50 Bangladesh J. Sci. Ind. Res. 51(1). 69-74, 2016